2017
DOI: 10.3906/sag-1512-65
|View full text |Cite
|
Sign up to set email alerts
|

Using fuzzy logic for diagnosis and classification of spasticity

Abstract: IntroductionSpasticity is a common sensory-motor control disorder characterized by increased velocity-dependent stretch reflex responses resulting from upper motor neuron (UMN) lesions (1). Spasticity is frequently observed in cases such as spinal cord injury, multiple sclerosis, traumatic brain damage, cerebral palsy, and stroke, which can be accompanied by cerebral and spinal pathology that is dispersed or regional (2). The pathophysiology of spasticity is complicated and it is rather difficult to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the medical and health sciences alone, we found 1124 publications addressing the problem of classification using fuzzy logic. These include the classification of rare diseases or the grouping of patients [46][47][48], but also geological [49,50], climatic phenomena [51,52], human behavior [53], or crop maturity classifications [54].…”
Section: Discussionmentioning
confidence: 99%
“…In the medical and health sciences alone, we found 1124 publications addressing the problem of classification using fuzzy logic. These include the classification of rare diseases or the grouping of patients [46][47][48], but also geological [49,50], climatic phenomena [51,52], human behavior [53], or crop maturity classifications [54].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the RMS and MNF also showed that the stroke affected the magnitude and frequency of the sEMG signals for the GS, but not for the BF ( Fig 5 ). Stroke led to decreased magnitude and frequency of GS, revealing atrophy of muscle fibers, lowered firing rate, weakened capacity of motor-units recruitment, reduced conduct velocity and muscle fatigue by hemiplegia for gait performance [ 15 , 24 ]. The stroke-induced neuromuscular abnormity in GS may result in less than necessary propulsion at the pre-swing phase and thus generate debilitated muscle force for knee flexion during swing stage, all of which could impair the AR of knee flexion in gait [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li and Hong found when stroke patients took negative-heeled shoes during walking the sEMG amplitudes of GS and BF increased, accompanied by greater knee flexion [ 14 ]. Other studies reported that it was the GS but not the BF that exhibited reduced sEMG amplitude and frequency with decreased knee motion in post-stroke gait [ 15 , 16 ]. These studies inspired us that to further examine the amplitude and frequency information underlying the sEMG signals of the involved muscles would help better understand the causes and solutions of stiff-knee gait in post-stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…As the LSTM network requires a sequence of data points to train the network, analysis is done on the behaviour of the signals for the various movements to unify them to a single value for each timestamp. Fuzzy Logic provides a means to perform this action in a more interpretable form based on its natural fluctuations[34,35].…”
mentioning
confidence: 99%